Kesan Estetika dan Fungsi JPO Pinisi Tanpa Atap di Jalan Sudirman: Perspektif Evaluasi Desain Kota untuk Mengoptimalkan Keamanan dan Kenyamanan Urban - Triana Amalia Putri; Mamluatul Uyun (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study analyzes the aesthetics of the roofless Pinisi Pedestrian Bridge in the Sudirman area as an element of public space that plays a role in shaping the visual quality and pedestrian experience in the city center. A qualitative approach was used to understand users' perceptions of the form, materials, structure, and visual impressions that emerged after the revitalization. Documentation and thematic analysis studies show that design changes have improved comfort, safety, and area identity, in line with previous studies emphasizing the importance of aesthetics in urban spaces. The results of the study show that the presence of visual elements that are in harmony with the surrounding environment can create a more organized flow of movement and a more attractive atmosphere for the community. The revitalization of the Pinisi pedestrian bridge also strengthens the image of the Sudirman area as a modern public space that supports pedestrian activity. These findings confirm that the integration of aesthetic value and function is key in designing pedestrian infrastructure that is adaptive to the needs of urban communities.